Sistem Monitoring Kegiatan Keagamaan Madrasah Ibtidaiyah Nurrohmah Bina Insani - Muhtar, Syifa' Ul Haq; Idris, Moh (E-Jurnal Universitas Samudra, 2025)
The MI Nurrohmah Bina Insani religious activity monitoring system is a web-based system that monitors religious activities carried out by students. This system is created to assist teachers and parents in monitoring students both at school and at home. The system is developed due to issues with the recording of student monitoring activities still using logbooks, which are prone to damage or loss. The monitoring includes daily monitoring and religious monitoring. The system will report the results of daily and religious monitoring activities carried out by students every day. Parents and teachers can directly view the monitoring reports through the provided system. This research focuses on the development of the MI Nurrohmah Bina Insani religious activity monitoring system. The system is developed using the waterfall method, and its system testing stage is conducted using black-box testing method.